East West 101 Episode 1-6 - Andrikidis, Peter; Pickering, Joseph; Hany, Don; MacInnes, William; Porter, Susie
Post 9/11, the London and Bali bombings, Muslims and non Muslims live side by side in a climate of fear. Zane Malik is a brilliant, but hot-headed, detective in the Major Crime Squad. Malik is also a Muslim. And at a time when just to be Arab is to arouse suspicion and fear, Malik feels under pressure to prove himself and his loyalty to the Force. Up against him is Snr Detective Crowley, a detective of the old school. Malik battles with Crowley as they investigate complex psychological crimes of love, betrayal and revenge. But Malik is driven by a secret personal quest. He intends to find the man who shot his father in a robbery when he was a child. He's using the skills he's gained as a cop to do it. But this journey will bring him face to face with all that he fears. [www.sbs.com.au]
Keywords: DVD-Video